Numerical Cognition Based on Precise Counting with a Single Spiking Neuron - Hannes Rapp; Martin Paul Nawrot; Merav Stern (iScience, 2020)
Summary: Insects are able to solve basic numerical cognition tasks. We show that estimation of numerosity can be realized and learned by a single spiking neuron with an appropriate synaptic plasticity rule. This model can be efficiently trained to detect arbitrary spatiotemporal spike patterns on a noisy and dynamic background with high precision and low variance. When put to test in a task that requires counting of visual concepts in a static image it required considerably less training epochs than a convolutional neural network to achieve equal performance. When mimicking a behavioral task in free-flying bees that requires numerical cognition, the model reaches a similar success rate in making correct decisions. We propose that using action potentials to represent basic numerical concepts with a single spiking neuron is beneficial for organisms with small brains and limited neuronal resources. : Neuroscience; Cognitive Neuroscience; In Silico Biology Subject Areas: Neuroscience, Cognitive Neuroscience, In Silico Biology